2019
DOI: 10.1111/cas.13924
|View full text |Cite
|
Sign up to set email alerts
|

Platforms of in vivo genome editing with inducible Cas9 for advanced cancer modeling

Abstract: The emergence of clustered regularly interspaced short palindromic repeat (CRISPR)/Cas9 technology has dramatically advanced how we manipulate the genome. Regarding in vivo experiments, Cas9‐transgenic animals could provide efficient and complex genome editing. However, this potential has not been fully realized partly due to a lack of convenient platforms and limited examples of successful disease modeling. Here, we devised two doxycycline (Dox)‐inducible Cas9 platforms that efficiently enable conditional gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 35 publications
2
12
0
Order By: Relevance
“…The mRNA for each of the point mutations ( Kras G12D and Kras G12C) was expressed in approximately 50% of cells within an adenocarcinoma carrying at least 1 copy of the gene. The difference in the indolence of each of the models, Kras G12D vs G12C and the Trp53 with Stk11 reveals a heterogeneity that has been reported by others [13, 17, 20] and likely results from differential usage of CRISPR-Cas9 double strand break repair mechanisms, homology directed repair, or non-homologous end joining, followed by different selective pressures over the heterogenous population of genetic mutations that arise in each model. This heterogeneity is unlike the results reported for other GEMMs and is an advantage of the inducible Cas9 systems [38].…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…The mRNA for each of the point mutations ( Kras G12D and Kras G12C) was expressed in approximately 50% of cells within an adenocarcinoma carrying at least 1 copy of the gene. The difference in the indolence of each of the models, Kras G12D vs G12C and the Trp53 with Stk11 reveals a heterogeneity that has been reported by others [13, 17, 20] and likely results from differential usage of CRISPR-Cas9 double strand break repair mechanisms, homology directed repair, or non-homologous end joining, followed by different selective pressures over the heterogenous population of genetic mutations that arise in each model. This heterogeneity is unlike the results reported for other GEMMs and is an advantage of the inducible Cas9 systems [38].…”
Section: Discussionsupporting
confidence: 54%
“…Moreover, as the system turns off upon withdrawal of dox it can be repeatedly activated for sequential editing of multiple genes, but more importantly inactivation minimizes unwanted downstream effects of the system and Cas9 exposure enabling purer efficacy studies. This emphasizes the advantage of the ODInCas9 inducible model over Cre activated Cas9 inducible systems that are constitutively active upon recombination [17, 18, 32, 33]. Tight regulation of Cas9 expression in the ODInCas9 system overcomes the leaky nature of Cre or Cas9 reported in other models [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous efforts to employ a DOX-inducible Cas9 approach for the conditional deletion of MCL-1 were hampered by inefficient induction of Cas9 expression [33]. In recent studies, robust expression of Cas9 in an in vivo Cas9 expressing mouse model was reported [34,35]. Here, we have demonstrated that our system permits effective, conditional expression of Cas9 in DLBCL cell lines.…”
Section: Discussionmentioning
confidence: 76%
“…Inducible expression systems including recombinase-mediated cassette exchange, Cre-recombinase, or tetracycline (Tet) sensitive systems, have been used to generate inducible Cas9 mice 12,13,[16][17][18][19][20][21] .…”
mentioning
confidence: 99%